New artery of knowledge: 3D models of angiogenesis. (19th December 2019) - Zucchelli, Eleonora; Majid, Qasim A; Foldes, Gabor
Abstract : Angiogenesis and vasculogenesis are complex processes by which new blood vessels are formed and expanded. They play a pivotal role not only in physiological development and growth and tissue and organ repair, but also in a range of pathological conditions, from tumour formation to chronic inflammation and atherosclerosis. Understanding the multistep cell-differentiation programmes and identifying the key molecular players of physiological angiogenesis/vasculogenesis are critical to tackle pathological mechanisms. While many questions are yet to be answered, increasingly sophisticated in vitro, in vivo and ex vivo models of angiogenesis/vasculogenesis, together with cutting-edge imaging techniques, allowed for recent major advances in the field. This review aims to summarise the three-dimensional models available to study vascular network formation and to discuss advantages and limitations of the current systems.